Unión entre teoría y práctica artística a partir del repliegue del arte sobre sí mismo y del concepto de la alotropía - Salamanca, Óscar (Universidad Antonio Nariño, 2021)
This article proposes and explores a form of union between artistic theory and practice, basedon the concept of allotropy taken by Gilles Deleuze from Burroughs’s work, through which critical and creative expressions on art remove traditional boundaries and merge into a bodydetached from the idea of an “organism” designed for a particular purpose, and that carrieswithin it the potential for multiple contingencies and experiments. At first, the text indicatesan historical context of secularization in which art and society are forced to rework theirmeanings, and finally, in consideration of the loss of a solid base of reference for artistic creation, the text proposes the Artaud’s idea of the body without organs, conceptually potentializedby Deleuze, as the sign of art in contemporary times.